2016
DOI: 10.1152/ajpheart.00796.2015
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinases 3-dependent microvascular endothelial cell barrier function is disrupted under septic conditions

Abstract: Sepsis is associated with dysfunction of microvascular endothelial cells (MVEC) leading to tissue edema and multiple organ dysfunction. Metalloproteinases can regulate MVEC function through processing of cell surface proteins, and tissue inhibitor of metalloproteinases 3 (TIMP3) regulates metalloproteinase activity in the lung following injury. We hypothesize that TIMP3 promotes normal pulmonary MVEC barrier function through inhibition of metalloproteinase activity. Naive Timp3(-/-) mice had significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 86 publications
3
34
0
Order By: Relevance
“…It has previously been shown that TIMP3 expression is reduced in atherosclerosis, abdominal aortic aneurysm and type 2 diabetes mellitus from human subjects or experimental models [10, 26, 27]. The abnormal TIMP3 expression served as a causal mediator of the corresponding pathophysiologic process [10, 11, 13, 15]. Notably, TIMP3 is highly expressed in heart, and its expression is also decreased in myocardial infarction animal model and heart failure patients [28, 29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been shown that TIMP3 expression is reduced in atherosclerosis, abdominal aortic aneurysm and type 2 diabetes mellitus from human subjects or experimental models [10, 26, 27]. The abnormal TIMP3 expression served as a causal mediator of the corresponding pathophysiologic process [10, 11, 13, 15]. Notably, TIMP3 is highly expressed in heart, and its expression is also decreased in myocardial infarction animal model and heart failure patients [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…The tissue inhibitor of metalloproteinases (TIMPs) plays a critical role in regulating MMPs activity and ECM formation, because the imbalance between MMPs and TIMPs markedly disrupts ECM integrity in multiple cardiovascular diseases [9, 10]. Among the four TIMPs, TIMP3 is a unique member, which not only inhibits MMPs activity, but also functions as a potent inhibitor of ADAMs [11, 12], indicating a crucial role of TIMP3 in the regulation of ECM deposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs modulate endothelial barrier integrity through processing of adherens and tight junction proteins (167). MMP-8 inhibition protects mice from death in sepsis (168170).…”
Section: Endothelial Response To Gcs In Sepsismentioning
confidence: 99%
“…Arpino and colleagues showed that inhibition of metalloproteinase-mediated adherens junctions’ disruption by tissue inhibitor of metalloproteinases-3 (TIMP-3) preserves normal endothelial barrier integrity. Pulmonary microvascular endothelial cells monolayers from TIMP-3 KO mice spontaneously displayed barrier dysfunction associated with disrupted surface VE-cadherin localization (167). …”
Section: Endothelial Response To Gcs In Sepsismentioning
confidence: 99%